Blood pressure control assessment among Type-2 diabetes patients: a preliminary retrospective cohort study in Kuantan, Pahang State, Malaysia - Abdullah, Fa’iza; Tin, Myo Han; Ismail, Ida Zuriaty; Md Aris, Mohd Aznan (2015)
Hypertension (HPT) is the most common co-morbidity among type 2 diabetes mellitus (T2DM) patients which causes increased risk of morbidity and mortality from stroke, heart failure and heart attack¹. Thus, keeping blood pressure within targeted control level is crucial to reduce the cardiovascular complications in T2DM patients. The HPT control status of DM patients should be assessed and analyzed to improve treatment outcomes.